Faktor-Faktor yang Memengaruhi Niat Konsumen untuk Membeli Produk Melalui E-Commerce - Ariansyah Ariansyah; Mukhamad Najib; Jono M Munandar (Jurnal Manajemen dan Organisasi, 2020)
The use of e-commerce in running a business has become a trend nowadays. This is marked by many consumers conducting online transactions to run their business or order the desired product because it is easy, fast and flexible. This study aims to analyze consumer characteristics, factors that influence the intention to buy products through e-commerce, and differences in consumers when shopping at malls and e-commerce. The approach in this study uses a quantitative approach with a survey method. This research was conducted using accidental sampling techniques with respondents totaling 121 people. This study uses primary data which is done by distributing questionnaires directly to respondents totaling 121 respondents consisting of 121 respondents to e-commerce users in the Jabotabek region. Data analysis was performed using SEM using Partial Least Square (PLS) software. This study shows that most consumers are students and domiciled in Bogor and do not have jobs yet. The objective norms and attitudes toward behavior have no significant effect on buying intentions, whereas only hypotheses related to perceptions of behavior control have been shown to have a significant effect on it. This means that consumers prefer shopping at the mall compared to shopping online.